Epigenetic landscape of germline specific genes in the sporophyte cells of Arabidopsis thaliana - Jung, Chol Hee; O'Brien, Martin; Singh, Mohan B.; Bhalla, Prem L. (Frontiers in Plant Science, 2015)
In plants, the germline lineages arise in later stages of life cycle as opposed to animals where both male and female germlines are set aside early in development. This developmental divergence is associated with germline specific or preferential expression of a subset of genes that are normally repressed for the rest of plant life cycle. The gene regulatory mechanisms involved in such long-term suppression and short-term activation in plant germline remain vague. Thus, we explored the nature of epigenetic marks that are likely associated with long-term gene repression in the non-germline cells. We accessed available Arabidopsis genome-wide DNA methylation and histone modification data and queried it for epigenetic marks associated with germline genes: genes preferentially expressed in sperm cells, egg cells, synergid cells, central cells, antipodal cells or embryo sac or genes that are with enriched expression in two or more of female germline tissues. The vast majority of germline genes are associated with repression-related epigenetic histone modifications in one or more non-germline tissues, among which H3K9me2 and H3K27me3 are the most widespread repression-related marks. Interestingly, we show here that the repressive epigenetic mechanisms differ between male and female germline genes. We also highlight the diverse states of epigenetic marks in different non-germline tissues. Some germline genes also have activation-related marks in non-germline tissues, and the proportion of such genes is higher for female germline genes. Germline genes include 30 transposable element (TE) loci, to which a large number of 24-nt long small interfering RNAs were mapped, suggesting that these small RNAs take a role in suppressing them in non-germline tissues. The data presented here suggest that the majority of Arabidopsis gamete-preferentially/-enriched genes bear repressive epigenetic modifications or regulated by small RNAs.